Exploring the Relationship Between Entrepreneurial Mindsets and Business Success: Implications for Entrepreneurship Education - Mesri Welhelmina Nisriani Manafe; Muammar Revnu Ohara; Silvy Sondari Gadzali; Muhammad Ade Kurnia Harahap; Abu Muna Almaududi Ausat (Departement of Mathematics Education, 2023)
Entrepreneurship is becoming an increasingly popular topic these days. Many people are interested in becoming an entrepreneur and developing their own business. However, not everyone has the ability to become a successful entrepreneur. There are several factors that can influence business success, one of which is having an entrepreneurial mindset. The purpose of this paper is to explore the relationship between entrepreneurial mindset and business success and to discuss the implications for entrepreneurship education. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. This study shows that there is a positive relationship between entrepreneurial mindset and business success. Entrepreneurial mindset consists of five main dimensions namely opportunity orientation, innovativeness, proactiveness, self-confidence and risk tolerance. Entrepreneurs who have a strong entrepreneurial mindset are more likely to achieve success in their business. The study also suggests that teaching entrepreneurship should focus on developing entrepreneurial mindset to prepare students to become successful entrepreneurs in the future.